(untitled) (Journal of Energy and Safety Technology (JEST), 2024)
This study examined how Sustainable Development Goal (SDG) 7 can achieveits goal in ASEAN, which is to ensure that everyone in the region has access to affordable, dependable, sustainable, and modern energy. To achieve the objective of this study, three SDG 7 indicators (2018-2021) were chosen: (i) the percentage of the population with access to electricity; (ii) the fraction of renewable energy in total final energy consumption; and (iii) energy intensity measured by primary energy and GDP. Critical Discourse Analysis (CDA) was employed as an approach in this study. According to the findings of this study, the discourses around SDG 7 have not adequately promoted collaborative efforts among stakeholders. As a result, SDG 7 may fall short of its goal of providing everyone with access to affordable, dependable, sustainable, and modern energy, leaving someone(s) behind. Thus, it is critical to shift the discourses surrounding SDG 7 to support the collective efforts, by bringing together multiple backgrounds, interests, and disciplines using an interdisciplinary approach.